Inclusive Approaches to Quranic Memorization: A Case Study of Tahfiz Methods for Learners with Disabilities - Muhammad Saminu; Zaifullah Athari; Sukree Langputeh (Journal of Theory and Research Memorization Quran, 2025)
Tahfiz Alquran is a fundamental tradition in Islamic education; however, for learners with disabilities, the memorization process requires adaptive and inclusive approaches. This study aims to analyze Quranic memorization methods applied to students with visual, hearing, and multiple disabilities, evaluate their effectiveness, and formulate implications for the development of inclusive tahfiz curricula. A qualitative case study method was employed, with data collected through teacher interviews, field observations in inclusive tahfiz institutions, literature review, documentation of Braille Quran and sign-language Quran manuscripts, and analysis of audio, visual, and tartil based learning practices. The findings reveal: i) audio-tartil methods, combining Braille Quran and murattal recitation, are effective for visually impaired learners; ii) visual-sign methods, such as Abata and sign-language Quran, assist hearing-impaired learners in recognizing letters and verses; iii) intensive repetition, family support, and the use of digital technologies (Braille Quran applications, sign-language videos) accelerate memorization; iv) spiritual motivation and inclusive environments are decisive factors for success. The novelty of this study lies in combining traditional tahfiz methods with digital tools and inclusive approaches. Its implications strengthen disability-friendly curricula, improve teacher skills, and support global inclusive education within the SDGs framework.